ANALISIS EFISIENSI TEKNIS PENGGUNAAN INPUT PRODUKSI USAHATANI BAWANG MERAH DI DESA GUNTARANO KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Laksmayani, Made Krisna (JSTT, 2015)
This study was conducted to determine the effect of production inputs (land, seed, fertilizer and labor) towards production of Shallot, the level of technical efficiency of farming Shallots and socioeconomic factors influence the level of technical efficiency Onion farm in the village of the District Guntarano Tanantovea Donggala. The research location is determined intentionally (purposive), with the consideration that that village is a center Guntarano onion production in Sub Tanantovea Donggala. Results of analysis in this study shows that the vast land, seed, fertilizer urea, fertilizer KCL, ZA fertilizer, organic fertilizer, and labor significantly affect production or variable (Y) with the coefficient of determination (R2) of 0.848 indicates that the variation factors of production onion (Y) can be explained by all the variables (Xi) of 84.8%, while 15.2% were caused by other factors not included in the model. Technical efficiency values obtained in this study amounted to 0.897, which means that it takes the addition of a good use of production inputs as well as social and economic factors. Social and economic factors also affect the production of onion in the village Guntarano (age of respondent, to farm experience, education level, frequency of follow agricultural extension, and the number of family dependents) to the onion production generated by the coefficient of determination (R2) of 0.510 indicates that the variation onion production factor (Y) can be explained by all the variables (Xi) amounted to 51.0%.